Efektivitas Terapi Kelompok terhadap Test Anxiety dan Self Efficacy pada Mahasiswa - Ilham Anggi Putra; Lifina Dewi Pohan (Universitas Kristen Maranatha, 2018)
School examination or test describes as an evaluative situation that requires students to do some task with certain limit of time and in a propriate place. Other wise, test or exam is one significant factors that influence higher level of test anxiety, so some students might fail on the test. Self efficacy plays an important role toward academic consistency, academic adjustment, better learning strategy and good academic function. The aim of this study is to decrease test anxiety and increase self efficacy among students with group therapy. The participant of this study characterized by high level of test anxiety and low self efficacy.. This study use single case AB design with 3 steps of measurement : baseline, 4 session execution and follow up. The results shown that group therapy effective to decreasing level of test anxiety and increasing level of self efficacy among college students.